UJI KADAR SULFAT PADA AIR MINUM DALAM KEMASAN (AMDK) SECARA SPEKTROFOTOMETRI UV-VIS - Ananda, Meita Sari (AMINA, 2019)
The goal of this study is to quantitaively determine both the concentration of sulfate (SO4-2) contained in bottled-drinking water (AMDK) via spectrophotometry UV-Vis and the quality of the water compared to Permenkes No. 429/MENKES/PER/IV/2010. The sample was mixed with BaCl2 to form BaSO4 which can be recognised by employing UV-Vis spectrophotometer at 420 nm wave length. The obtained absorbance data were then applied to the linear equation proposed by using standard sulfate solution. The analysis shows that the various products of AMDK consumed Acehnese people contain sulfate in low level, numerically under 0,0397 ppm. Thie research conclude that the AMDK is safe to be consumed daily.